UPAYA PENINGKATAN HASIL BELAJARÂ SISWA DALAM PEMBELAJARANÂ PASSING BAWAH PERMAINAN BOLA VOLI MELALUI PENDEKATAN BERMAIN PADA SISWA KELAS V SDN DUKUH KUPANG IV / 491 SURABAYA - SUYONO, (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education in schools is of significant importance to education as a whole. The existence of physical education in schools not only improve health and physical fitness, but also provide experience in the cognitive, affective and psychomotor for children. To achieve the successful teaching of physical education in schools, there are other factors, including: teachers, students, facilities and infrastructure and curriculum. One way to achieve the goal of teaching physical pendidilan is to implement a method that readily accepted by students. One alternative to facilitate the delivery of content from teacher to students is to use learning methods are easy to understand olegh students. Learning methods are given to the students are expected to achieve the goals in physical education and is also expected students can obtain easiness in learning because the main emphasis in this method is to create an atmosphere of joy and delight at the elementary school students and encourages students to participate , creative and communicative.      The purpose of this research is to improve student learning outcomes in learning the technique of passing a volleyball game play approach. The research location in SDN Dukuh Kupang IV/491 Surabaya. The subjects consisted of 38 students of SDN Dukuh  Kupang IV/491 Surabaya. Of the increase and the procedures that have been performed, the learning model used is the approach play.         From the results of this study in order to obtain a description of the learning process more effective and provide optimistic results, al for students, it needs to be delivered is at the time of applying the model of learning through play approach teacher should prepare well before implementing that learning to maximize learning out comes and teachers always creates a fun learning environment so as to eliminate boredom in a student       Keywords : passing down, play approach